Greening for academic achievement: Prioritizing what to plant and where - Kuo, Ming; Klein, Samantha; Browning, Matthew; Zaplatosch, Jaime (Landscape and Urban Planning, 2020)
Converging evidence from hundreds of studies suggests that contact with nature enhances learning in elementary and high school students-could greening in and around schoolyards improve academic achievement in sixth grade students, many of whom are negotiating the transition from elementary to middle school? This study examines the greenness-academic achievement relationship in 450 public schools in Washington State using two different measures of greenness (tree canopy cover and total green cover as assessed via NDVI), at two different scales (250m and 1000m radial buffers around a school), with two different measures of school achievement (the percentage of students meeting or exceeding state standards in reading and math). Six of eight spatial error models showed statistically significant, positive relationships between school greenness and achievement in sixth-graders-tree canopy within 250m of a school predicted better performance in both reading and math, as did total greenness within 250m, and tree canopy within 1000m-even after controlling for 17 potential confounders, including student characteristics, school resources, size, and location. Further analyses suggest that the greenness-achievement ties are primarily driven by the tree cover within 250m of a school. If a community wanted to experiment with greening schools for academic achievement, these findings provide clues as to what might be best to plant and where, suggesting that planting trees within 250m might maximize any effect on achievement.